Aspek Hukum Akta Notaris pada Jual Beli Tanah Berstatus Letter C - Ivannia Cendranita; Saiful Anwar (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
Agrarian problems are problems or disputes regarding agrarian objects, which often occur, namely disputes regarding ownership of their land rights, including the transfer of land rights through sale and purchase with the object of Letter C land. Based on this context, the author will discuss the validity of notarial deed against sale and purchase of land letter c object. The method used is normative juridical with a statutory approach, conceptual approach, and case approach. The study understands the concept of the validity of a notarial deed against the object of the Letter C of the land under study, then describes the relevant legal materials that have been obtained and then clarified based on the formulation of the problem. The results of the study show that a sale and purchase deed with a Letter C land object is considered valid if it meets the legal requirements of an agreement based on Article 1320 BW, and in the practice of buying and selling land objects that have not been titled based on customary law has fulfilled the principles of light, cash and real, and in the process of registering a certificate for the first time must attach complementary documents. The authority to make a Sale and Purchase Deed if the land object has not been titled or Letter C / Girik / Petok, the majority of which are located in the village, the sale and purchase deed can be made by PPAT Camat. The suggestion in this research is that people who will or want to trade their land, should avoid buying and selling with a deed under the hand, this will result in the land object being vulnerable to disputes because it does not have strong evidence to prove ownership of land rights, it would be better to sell and buy land according to the regulations set by the government.